2014
DOI: 10.1007/s11010-013-1952-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypoxia exposure on the recovery of skeletal muscle phenotype during regeneration

Abstract: Hypoxia impairs the muscle fibre-type shift from fast-to-slow during post-natal development; however, this adaptation could be a consequence of the reduced voluntary physical activity associated with hypoxia exposure rather than the result of hypoxia per se. Moreover, muscle oxidative capacity could be reduced in hypoxia, particularly when hypoxia is combined with additional stress. Here, we used a model of muscle regeneration to mimic the fast-to-slow fibre-type conversion observed during post-natal developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 37 publications
0
17
1
Order By: Relevance
“…Our results revealed that hypoxia delayed the formation and growth of new myofibers during the first week after injury, but did not affect the final recovery of muscle mass and the fiber cross‐sectional area after 4 wk (45). Our results also indicate that hypoxia delays the recovery of the oxidative capacity of regenerated muscle without affecting the maturation of its contractile phenotype (i.e., the transition from fast to slow MHC isoforms observed during muscle regeneration) (7). Similarly, it was demonstrated that the formation of myotubes, which was repressed during the early phase of differentiation at low O 2 level (0.5% O 2 ) in vitro , was able to progress during the late phase (12 d ) (41).…”
Section: Skeletal Muscle Regeneration and Effects Of Low O2 Levelsmentioning
confidence: 64%
See 3 more Smart Citations
“…Our results revealed that hypoxia delayed the formation and growth of new myofibers during the first week after injury, but did not affect the final recovery of muscle mass and the fiber cross‐sectional area after 4 wk (45). Our results also indicate that hypoxia delays the recovery of the oxidative capacity of regenerated muscle without affecting the maturation of its contractile phenotype (i.e., the transition from fast to slow MHC isoforms observed during muscle regeneration) (7). Similarly, it was demonstrated that the formation of myotubes, which was repressed during the early phase of differentiation at low O 2 level (0.5% O 2 ) in vitro , was able to progress during the late phase (12 d ) (41).…”
Section: Skeletal Muscle Regeneration and Effects Of Low O2 Levelsmentioning
confidence: 64%
“…9 for a recent review). In our recent studies, we did not observe any signs of regeneration in skeletal muscles (control soleus and plantaris muscles) from rats exposed to severe hypobaric hypoxia (7, 8, 13, 45), suggesting that hypoxia per se does not trigger muscle regeneration in animals.…”
Section: Skeletal Muscle Regeneration and Effects Of Low O2 Levelsmentioning
confidence: 67%
See 2 more Smart Citations
“…In particular, PGC-1α regulates oxidative phosphorylation, mitochondrial biogenesis and respiration (22,23). Numerous previous studies have suggested that ischemia and hypoxia significantly induce the expression of PGC-1α (5)(6)(7)(8)(9)(10)(11)24,25). Arany et al (12) reported that PGC-1α was able to upregulate the expression of angiogenic factors such as VEGF, and promote the formation of new blood vessels in skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%